2004
DOI: 10.1128/jvi.78.17.9030-9040.2004
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hepatitis C Virus-Like Particle Binding to Target Cells by Antiviral Antibodies in Acute and Chronic Hepatitis C

Abstract: Hepatitis C virus (HCV) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 56 publications
5
50
2
Order By: Relevance
“…More relevant systems are based on generation of HCV-like particles and their interactions with susceptible cells (46), such as noninfectious HCV-like particles (6,44) and infectious HCVpp (4,5). These systems have shown that antibodies against the E1 and E2 glycoproteins could prevent entry of HCV-like particles into cells (3,30,43,49). Using the HCVpp system, we have demonstrated that HCV-AB 68 and HCV-AB 65 were able to neutralize HCVpp genotype 1 infection of Huh-7 cells by 60 to 5 HCV RNA copies/ml were preincubated with 100 to 400 g/ml of a 1:1 (mg/mg) mixture of HCV-AB 68 and HCV-AB 65 and subsequently used to infect normal human liver fragments ex vivo.…”
Section: Discussionmentioning
confidence: 99%
“…More relevant systems are based on generation of HCV-like particles and their interactions with susceptible cells (46), such as noninfectious HCV-like particles (6,44) and infectious HCVpp (4,5). These systems have shown that antibodies against the E1 and E2 glycoproteins could prevent entry of HCV-like particles into cells (3,30,43,49). Using the HCVpp system, we have demonstrated that HCV-AB 68 and HCV-AB 65 were able to neutralize HCVpp genotype 1 infection of Huh-7 cells by 60 to 5 HCV RNA copies/ml were preincubated with 100 to 400 g/ml of a 1:1 (mg/mg) mixture of HCV-AB 68 and HCV-AB 65 and subsequently used to infect normal human liver fragments ex vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Fixation and immunostaining of Huh7.5 cells was performed using monoclonal anticore Abs (C1/C2) as described recently (25,28,29). Cells were embedded in fluorescence-mounting medium containing DAPI (4 -6-daimidino-2-phenylindole; Vector Laboratories) for cell nuclei staining.…”
Section: Immunofluorescence Staining Of Viral Proteins In Infected Homentioning
confidence: 99%
“…However, surrogate models of infection, such as animal infection and cell and receptor binding assays, have highlighted the potential role of antibodies in both acute and chronic infection (6,24,25,36,55,57,63,68,69). It is important to note that not all antibodies that inhibit binding of virus ligand to cell and/or receptors in in vitro assays necessarily neutralize infection.…”
mentioning
confidence: 99%